Prevalence of Depression in Migraine Patients: A Multicentre Cross-Sectional Study from Pakistan - Ziaullah, Inayatullah Awan, Abid Usman, Kauser Mahmood, Lalchand, Muhammad Firaz Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study was to determine the frequency of depression in patients with migraine visiting to Neurology outpatient department. Study Design: Cross-sectional Place of study: Data was collected from different tertiary care hospitals of Pakistan, including Lady Reading Hospital, Peshawar, Ghulam Mahar medical college and United medical and Dental College, Karachi, during period from November, 2021 to April, 2022. Methods: Total 425 patients of both genders had age 18-70 years were included in this study. Included patients had migraine and visited outpatient department of Neurology. After obtaining informed written consent detailed demographics of enrolled cases included age, sex, education status and place of living were recorded. Frequency and severity of depression among all cases were assessed. SPSS 24.0 was used to analyze all data. Results: Among 425 patients, 265 (62.4%) were males and 160 (37.6%) patients were females.Mean age of the patients was 29.7±10.50 years with mean BMI 23.7±11.26 kg/m2. 230 (54.1%) were married and 195 (45.9%) were unmarried. There were 215(50.6%) patients educated and 210 (49.4%) cases were non-educated. 180 (42.4%) patients had migraine with aura and 245 (57.6%) patients were without aura. We found that 300 (70.6%) patients had depression among all cases. Among 300 cases of depression, frequency of mild was 75, moderate was 125 and severity of depression was found in 100 cases. Conclusion: We came to the conclusion that since migraine sufferers had a relatively high rate of depression, there may be a connection between migraine and depression. When assessing migraine patients for a favorable prognosis and appropriate illness care, depression shouldn’t be disregarded. Keywords: Depression, Migraine, Aura